Bone Morphometric Evaluation around Immediately Placed Implants Covered with Porcine-Derived Pericardium Membrane: An Experimental Study in Dogs - Jimbo, Ryo; Marin, Charles; Witek, Lukasz; Suzuki, Marcelo; Tovar, Nick; Chesnoiu-Matei, Ioana; Dragan, Irina Florentina; Coelho, Paulo G. (International Journal of Biomaterials, 2012)
Objective. To investigate whether porcine-derived bioresorbable pericardium membrane coverage enhances the osseointegration around implants placed in fresh extraction sockets. Study Design. Twenty-four commercially available endosseous implants were placed in the fresh extraction sockets of the mandibular first molar of mature beagles (n=6). On one side, implants and osteotomy sites were covered with porcine-derived bioresorbable pericardium membranes, whereas on the other side, no membranes were used. After 6 weeks, samples were retrieved and were histologically processed for histomorphometric analysis. Results. The histological observation showed that bone loss and soft tissue migration in the coronal region of the implant were evident for the control group, whereas bone fill was evident up to the neck of the implant for the membrane-covered group. Bone-to-implant contact was significantly higher for the membrane-covered group compared to the control group, 75% and 45% (P<0.02), respectively. Conclusion. The experimental membranes proved to regenerate bone around implants placed in fresh extraction sockets without soft tissue intrusion.